Efektivitas Teknik Pembelajaran Berbasis Multimedia Terhadap Kualitas Pembelajaran PAI di SD INP. 12/79 Jeppe’e Kecamatan Tanete Riattang Barat Kabupaten Bone - Sania, Sania (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study examines the effectiveness of Multimedia-based learning techniques on the quality of PAI learning in elementary school. Research is included in the type of experimentation closely in testing a hypothesis in order to find influence, relationships, or differences in changes to the group subject to treatment. Research location of SD INP. 12/79 Jeppe'e Tanete Riattang West District Bone research results showed that the results of the learning scores of students of SD INP grade VI. 12/79 Jeppe'e Tanete Riattang West District Bone District, both Pretes score and postes student grade experiments as well as score pretes and postes control classes can be noted that the calculated T score obtained by 8.266 with Sig (2 tailed) = 0.000. At a significant level of 95% with D. B. 25 acquired t table = 1.71. So, T count (8.266) T table (1.71) or sig (2 tailed) (0.000) (0.05). Based on the above calculations, H0 is rejected and H1 is accepted. Thus, it is found that the multimedia-based learning techniques have a positive influence on the improvement of learning outcomes of class VI students in PIE learning at SD INP. 12/79 Jeppe'e Tanete Riattang West (H1) subdistrict. The average student PIE study that follows learning with multimedia-based learning techniques is higher than the average learning outcomes of students who do not follow multimedia-based learning techniques. Thus, the results of the PAI learning in SD INP. 12/79 Jeppe'e Tanete Riattang West Sub-district which follows learning with multimedia-based learning techniques is higher than that of students who follow PAI learning with other techniques.Penelitian ini menguji efektivitas teknik pembelajaran berbasis Multimedia pada kualitas pembelajaran PAI di sekolah dasar. Penelitian termasuk dalam jenis eksperimen yang dekat dalam menguji hipotesis untuk menemukan pengaruh, hubungan, atau perbedaan dalam perubahan pada kelompok yang menjalani pengobatan. Lokasi penelitian SD INP. 12/79 Hasil penelitian Jeppe'e Tanete Riattang District District Bone menunjukkan bahwa hasil skor pembelajaran siswa SD INP kelas VI. 12/79 Jeppe'e Tanete Riattang Distrik Tulang Barat Distrik, baik skor Pretes dan postes kelas eksperimen siswa maupun skor pretes dan kelas kontrol postingan dapat dicatat bahwa skor T yang dihitung diperoleh sebesar 8,266 dengan Sig (2 tailed) = 0,000. Pada tingkat signifikan 95% dengan D. B. 25 diperoleh t tabel = 1.71. Jadi, T hitung (8,266) T tabel (1,71) atau sig (2 tailed) (0,000) (0,05). Berdasarkan perhitungan di atas, H0 ditolak dan H1 diterima. Dengan demikian, ditemukan bahwa teknik pembelajaran berbasis multimedia memiliki pengaruh positif pada peningkatan hasil belajar siswa kelas VI dalam pembelajaran PIE di SD INP. 12/79 Kecamatan Jeppe'e Tanete Riattang Barat (H1). Rata-rata studi PIE siswa yang mengikuti pembelajaran dengan teknik pembelajaran berbasis multimedia lebih tinggi daripada rata-rata hasil belajar siswa yang tidak mengikuti teknik pembelajaran berbasis multimedia. Dengan demikian, hasil pembelajaran PAI di SD INP. 12/79 Jeppe'e Tanete Riattang, Kecamatan Barat yang mengikuti pembelajaran dengan teknik pembelajaran berbasis multimedia lebih tinggi daripada siswa yang mengikuti pembelajaran PAI dengan teknik lain.